Competing for Criminal Money - G. Rawlings; Brigitte Unger (Utrecht University, Utrecht School of Economics, Tjalling C. Koopmans Research Institute, 2005)
To compete for criminal money by means of low bank secrecy seems a tempting strategy for countries in order to attract additional funds. We show in a model that this "Seychelles-strategy" can increase national output, in particular if a country takes a (Stackelberg ) leadership in the competition game. If all countries try to do the same, there will be a race to the bottom and a supranational authority like the FATF (Financial Action Task Force) must intervene. However, there are also some intrinsic barriers to the "Seychelles-strategy". Among others, criminal capital might crowd out legal capital and money laundering might increase crime. Our findings suggest that countries have created niches for laundering. Small countries can free ride for a while, but eventually will face external sanctions and internal crime problems.
Keywords: 330